The Chinese Approach to Capital Inflows : Patterns and Possible Explanations - Wei, Shang-Jin (IMF Working Papers; Working Paper ;, 2005)
In this paper, we adopt a cross-country perspective to examine the evolution of capital flows into China, both in terms of volumes and composition. China's inflows have generally been dominated by foreign direct investment (FDI), a pattern that appears to be favorable in light of the recent literature on the experiences of developing countries with financial globalization. We provide a detailed documentation of the evolution of China's capital controls, a proximate determinant of the pattern of capital inflows. We also discuss a number of other intriguing hypotheses that attempt to capture the "deeper" causes underlying China's approach to capital flows. In particular, we argue that some popular mercantilist-type arguments are inconsistent with the facts. We also analyze the recent rapid rise of China's international reserves and discuss its implications. Contrary to some popular perceptions, the dramatic surge in foreign exchange reserves since 2001 is mainly attributable to non-FDI capital inflows, rather than current account surpluses or FDI.